The Impact of Ancient Landscape Changes on the City Arrangement of the Early Shang Dynasty Capital Zhengzhou, Central China - Chen, Panpan; Lu, Peng; Yang, Shugang; Storozum, Michael; Yang, Ruixia; Tian, Yan; Wang, Hui; Wu, Qian; Xu, Junjie; Wang, Xia; Yan, Lijie; Zhai, Haiguo (Frontiers in Earth Science, 2021)
Buried underneath modern Zhengzhou city in Henan Province, China, lies the archeological remains of one of the ancient capital cities of the Shang dynasty (1766 – 1122 BCE). Although it is likely that people planned this Shang capital city according to the demands of the surrounding environment, there is no clear relationship between the current environment, such as the hydrology and topography, and the ancient city’s layout. To better understand the relationship between planning principles used during the Shang dynasty and the nearby environment at Zhengzhou, we measured and sampled stratigraphic exposures at excavation locations throughout Zhengzhou. Through these excavations we obtained both absolute and relative chronological data from each culture layer, enabling us to use geospatial interpolation and analysis methods to reconstruct the ancient landscape. The results show that ancient city’s different activity areas had a close relationship with their environmental context. For example, the Shang dynasty palace was located on high ground and workshops were located down below along the courses of ancient rivers. In conclusion, we argue that research that merges geomorphology and archeology is a necessary prerequisite for understanding the development of urban areas.